Cochlear Reimplantation Rate and Cause: a 22-Year, Single-Center Experience, and a Meta-Analysis and Systematic Review. Issue 1 (15th August 2022) - Liu, Haotian; Yao, Xinyi; Kong, Weili; Zhang, Lin; Si, Jingyuan; Ding, Xiuyong; Zheng, Yun; Zhao, Yu
Abstract : Objectives: In terms of cochlear reimplantation, there is no consensus on the definition, range, or calculation formulation for the reimplantation rate. This study aims to put forward a relatively standardized and more explicit definition based on a literature review, calculate the rate of cochlear reimplantation, and examine the classification and distribution of the reimplantation causes. Design: A systematic review and retrospective study. A relatively clearer definition was used in this study: cochlear reimplantation is the implantation of new electrodes to reconstruct the auditory path, necessitated by the failure or abandonment of the initial implant. Seven English and Chinese databases were systematically searched for studies published before July 23, 2021 regarding patients who accepted cochlear reimplantation. Two researchers independently applied the inclusion and exclusion criteria to select studies and complete data extraction. As the effect size, the reimplantation rate was extracted and synthesized using a random-effects model, and subgroup and sensitivity analyses were performed to reduce heterogeneity. In addition, a retrospective study analyzed data on cochlear reimplantation in a tertiary hospital from April 1999 to August 2021. Kaplan-Meier survival analysis and the log-rank test were adopted to analyze the survival times of cochlear implants and compare them among different subgroups. Results: A total of 144 articles were included, with 85, 851 initial cochlear implantations and 4276 cochlear reimplantations. The pooled rate of cochlear reimplantation was 4.7% [95% CI (4.2% to 5.1%)] in 1989 to 2021, 6.8% [95% CI (4.5% to 9.2%)] before 2000, and 3.2% [95% CI (2.7% to 3.7%)] after 2000 ( P =0.003). Device failures accounted for the largest proportion of reimplantation (67.6% [95% CI (64.0% to 71.3%)], followed by medical reasons (28.9% [95% CI (25.7% to 32.0%)]). From April 1999 to August 2021, 1775 cochlear implants were performed in West China Hospital (1718 initial implantations and 57 reimplantations; reimplantation rate 3.3%). In total, 45 reimplantations (78.9%) were caused by device failure, 10 (17.5%) due to medical reasons, and 2 (3.5%) from unknown reasons. There was no difference in the survival time of implants between adults and children ( P = 0.558), while there existed a significant difference between patients receiving implants from different manufacturers ( P < 0.001). Conclusions: The cochlear reimplantation rate was relatively high, and more attention should be paid to formulating a standard definition, calculation formula, and effect assessment of cochlear reimplantation. It is necessary to establish a sound mechanism for long-term follow-up and rigorously conduct longitudinal cohort studies.